Mixed Aryl Phosphonate Prodrugs of a Butyrophilin Ligand - Foust, Benjamin J. (ACS Med Chem Lett, 2017)
[Image: see text] Studies of aryl phosphonate derivatives of a butyrophilin 3A1 ligand have resulted in identification of a potent stimulant of Vγ9 Vδ2 T cells. This compound, a mixed ester bearing one pivaloyloxymethyl substituent and one 1-naphthyl ester displayed an EC(50) of 0.79 nM as a stimulant of T cell proliferation, and a 9.0 nM EC(50) in an assay designed to measure interferon gamma production. In both assays, this is the most potent butyrophilin ligand prodrug yet reported, and thus it should be a valuable tool for studies of T cell function. Furthermore, mixed aryl/acyloxyalkyl esters may represent a new class of phosphonate prodrugs with high efficacy.